PROTECTIVE EFFECT INDUCED BY THE NEW SUBUNIT TUBERCULOSIS VACCINE WHEN USED AS A BCG BOOST IS ASSOCIATED WITH INHIBITION OF MYCOBACTERIAL DISSEMINATION - Vladimir Yeremeev (Medicinskaâ Immunologiâ, 2019)
Since 1924, BCG vaccine is used to protect children from the most severe forms of tuberculosis. At the same time, the protective effect of BCG in adults is variable. The potential for revaccination with live vaccine is further limited by the rapid spread of HIV infection. The early-secreted Mycobacterium tuberculosis proteins have been used extensively in TB vaccine development, due to their high immunogenicity and have shown protective effect in animal models. The aim of our study was to evaluate the opportunity to increase the anti-TB resistance in experimental animals by re-vaccination with a new subunit vaccine preparation following primary immunization with BCG. To perform such boost vaccination, we used a combination of the Ag85B-TB10.4-FliC chimeric protein, and the plasmid DNA encoding Ag85A antigen. Efficiency of the boost vaccination was evaluated in a model of M. tuberculosis H37Rv aerosol infection of C57BL / 6 laboratory mice, either in the intact animals, or those vaccinated with BCG only, or BCG followed by revaccination with the test vaccine. The data concerning mycobacteria outgrowth from the organs, and life-span of animals after infection were subject to comparative analysis. We have demonstrated that additional boost vaccination with the vaccine under study, as compared with conventional BCG vaccination, leads to further inhibition of mycobacteria dissemination from the site of infection, and significantly prolonged survival of infected animals.